Teaching object-oriented programming using BETA - Knudsen, Jørgen Lindskov; Madsen, Ole Lehrmann; Nørgaard, Claus; Petersen, Lars Bak; Sandvad, Elmer (DAIMI Report Series, 1990)
This paper describes the approach to teaching object-oriented programming at Aarhus University. This includes a brief discussion of the conceptual approach to teaching object-oriented programming. The BETA language is used as a basis for the teaching. The paper includes a brief description of BETA. Finally a presentation of the BETA Macintosh environment is given. This environment makes it easy for students to create object-oriented applications.